Competencias socioemocionales mediante el uso de recurso educativo WIX en estudiante de Básica Primaria (2019)
Emotional education is an indispensable complement in cognitive development and a fundamental prevention tool, since many problems have their origin in the emotional field. (Unesco, 1996) That is why this research work sought to generate spaces, instruments, mechanisms and ICT-mediated strategies specifically the Wix platform for the development of socio-emotional competencies in students of 4th grade ITI José Castillo Bolívar of the municipality of Soledad, based on the one hand, on important theoretical approaches and on recognized studies such as the model of the socio-emotional competencies of Rafael Bisquerra, the emotional intelligence model of Salovey and Mayer, the emotional intelligence model of Daniel Goleman and other important authors who nurtured this initiative. Descriptive explicative type research carried out under a mixed approach, within the complementary paradigm, this in order to preserve epistemological cohesion with the applied design. In this sense, the quantitative approach was used when analyzing, with descriptive statistics, the development of students' socio-emotional skills, comparing the results of the initial diagnosis with the results of the fine survey; Similarly, this work is carried out under the qualitative approach that, according to Sampieri (1998) is used for data collection without numerical measurement to cover or refine research questions in the research process. With the actions implemented, we sought to influence the development of socio-emotional skills in students to deliver integral people to society.